Penerapan Model Pembelajaran Snowball Throwing untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas 6 SDN 56 Talang Silungko 1 - Tobri, M. (CV. Master Literasi Indonesia, 2025)
This study was motivated by the low mathematics learning outcomes of sixth-grade students at SDN 56 Talang Silungko 1, particularly in the topic of fraction operations. To address this issue, the Snowball Throwing learning model was implemented to enhance student engagement and understanding through interactive and cooperative group activities. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The research subjects were 14 students. Data collection techniques included observation, tests, and documentation. The results showed that in the first cycle, 8 students (57,1%) achieved the Minimum Mastery Criteria (MMC), which increased to 12 students (92,9%) in the second cycle. This improvement indicates that the Snowball Throwing model successfully created a more active, collaborative, and constructive learning environment. Therefore, it can be concluded that the Snowball Throwing model is effective in improving mathematics learning outcomes and is recommended for broader implementation across various subjects and educational levels.